Motor performance and physical activity habits of college students in Costa Rica - Jiménez-Díaz, Judith; Morera-Castro, Maria (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2016)
The purpose of this study was to analyze the motor performance of fundamental motor skills and physical activity habits of students at the University of Costa Rica. A total of 92 males and 48 females (M age = 19.78 yr., SD = 4.72 yr.) enrolled in different Sports Activity courses taught at the Rodrigo Facio campus was assessed. The Instrument for the Evaluation of Fundamental Movement Patterns was used to assess motor performance in eight fundamental movement patterns (running, jumping, galloping, catching, throwing, bouncing, and kicking). The physical activity level was obtained from a self-reported questionnaire developed for such purpose. Results show that 28% of the participants were physically active. Participants presented a proficient performance in kicking, running, and galloping, but a non-proficient performance in jumping, hopping, bouncing, throwing and catching. Physical activity behavior was related to the overall performance of the motor skills assessed (Rho = .233; p = .006). In conclusion, college students presented a proficient performance on three of the eight skills assessed. In addition, a relationship was found between physical activity levels and performance. Physical Education teachers are recommended to develop activities to enhance motor performance of fundamental motor skills in college students.